Loans for the president: External debt and power consolidation in Egypt - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2022)
Egyptian President Abdel Fatah al-Sisi has consolidated his authoritarian regime in recent years. This has been accompanied by a significant increase in Cairo's foreign debt, which more than tripled between June 2013 and March 2022. The country's debt policy was directly linked to the presidential centre of power. The government managed a well-choreographed mix of incentives, threats, and concealment that made it possible to take out more and more new loans. The Egyptian military, on whose support President Sisi is dependent in order to assert his claim to power, is the main beneficiary of the debt policy. External debt helped to protect the revenues and assets of the armed forces, to finance major projects in which they could earn significant money, and to pursue an expansive military build-up. The instrumentalisation of debt policy for power politics increases the risk that Egypt will no longer be able to service its liabilities in the future. Above all, however, the misallocation of scarce financial resources undermines the socio-economic development of the country and promotes police-state repression. The latter, in turn, favours the political instrumentalisation of debt policy for power politics, as it prevents any control of government action. In the future, Germany and its European partners should therefore tie bilateral lending as well as support for Egypt in its negotiations with international financial institutions to two conditions: firstly, the dismantling of military economic activities - whereby the assets of the armed forces must also be disclosed - and secondly, concrete steps towards ending police-state repression.
Keywords: 320; Egypt; President Abdel Fatah al-Sisi; authoritarian regime; debt policy; power politics; international financial institutions; International Monetary Fund (IMF); Egyptian military; EU; bilateral lending